Predicting Hmong Male and Female Youth's Delinquent Behavior: An Exploratory Study. - Zha Blong Xiong; Ju-Ping Huang (Hmong Studies Journal, 2011)
Asian Americans have been viewed as a "model" minority by mainstream Americans for decades. Contrary to the model minority stereotype, however, Asian youth, especially Hmong and other Southeast Asians, are increasingly involved in crimes and delinquent activities. Yet, little research has focused on them, particularly Hmong youth. The present study addressed this gap in the literature by exploring the relative importance of individual, peer, family, and school factors in explaining Hmong youth's delinquent behavior in both male and female. Two hundred and six Hmong youth (115 males and 91 females), ages ranged from 11 to 25 years old, from Minnesota participated in the survey. The survey results showed that antisocial attitudes, academic achievement, and the lack of the mother's monitoring were the three factors that significantly explained youth's chances of being involved in delinquent acts regardless of their gender. However, when the youth were examined separately by gender, the results showed significant variations. The study ends with a few strategies offered for parents and school officials to prevent and intervene with delinquent behavior in the Hmong community.